Analysis of news published in the media about the grouper (Epinephelus marginatus) (Research, Society and Development, 2022)
The objective of this research was to carry out a news content analysis published in the media related to Epinephelus marginatus, a marine fish specie present on the Brazilian coast, which has high commercial value, good market acceptance and has a partially developed technological package. The results indicate that initiatives are being carried out to promote their reproduction in captivity and also to guarantee the repopulation of some regions affected by artisanal and industrial fishing. These activities are carried out with the aim of preserving and recovering marine ecosystems and boosting national marine fish farming, as an alternative to extractivism and the conservation of the species that is on the list of species threatened with extinction due to human action.